Formation of RNA G-wires by G₄C₂ repeats associated with ALS and FTD - Bose, Krishnashish (2022)
In the neurodegenerative disorders amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), expansion of the G4C2 hexanucleotide repeat in the gene C9orf72 is a most common known cause of the disease. Here we use atomic force microscopy (AFM) and gel electrophoresis to visualize the formation of higher-order structures by RNA G4C2 repeats in physiologically relevant conditions. For the RNA sequence r[G4C2G4], we observed G-wires with left-handed undulating features of 4.4-nm periodicity and a uniform height which is consistently higher than that of a duplex B-DNA. These higher-order structures were not degraded fully when treated with a mixture of RNase A and RNase T1. Similarly, higher-order structures were observed for sequences containing three or four G4C2 repeats, pointing towards their potential formation in longer sequence contexts. Our observations suggest that RNA G-quadruplex blocks and G-wires can accumulate in cells containing G4C2 repeat transcripts.